2021
DOI: 10.1039/d1sm00269d
|View full text |Cite
|
Sign up to set email alerts
|

Radiation curable polysiloxane: synthesis to applications

Abstract: Among the different types of specialty polymers, polysiloxane finds its position in the pyramid's apex in performance attributes. Unique structural features result in superior performance benefits over wide operational conditions....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Several studies have reported the preparation of hydrophobic DN ion gels by the introduction of various nanomaterial networks, including silica nanoparticles (NPs) [28][29][30] and TEMPOoxidised cellulose nanofibres. 31 The results of these studies revealed that the presence of hydroxyl groups on the surface of the nanomaterials is essential for the formation of nanoparticle networks in ILs and realising the toughening of ion gels. However, the relationship between the shape of nanoparticles of the brittle network and the macroscopic mechanical properties of the gels has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the preparation of hydrophobic DN ion gels by the introduction of various nanomaterial networks, including silica nanoparticles (NPs) [28][29][30] and TEMPOoxidised cellulose nanofibres. 31 The results of these studies revealed that the presence of hydroxyl groups on the surface of the nanomaterials is essential for the formation of nanoparticle networks in ILs and realising the toughening of ion gels. However, the relationship between the shape of nanoparticles of the brittle network and the macroscopic mechanical properties of the gels has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…UV-curing systems are mainly divided into two parts, free radicals polymerization [20,21] and cationic polymerization [22,23]. To obtain UV-curable transparent polysiloxanes, photosensitive functional groups such as (meth)acryloyloxy groups, thiol-ene groups, or epoxy groups should be introduced [24][25][26][27]. Presently, lots of researches and industrial applications are based on free radical induced (meth)acrylates polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned Si-O-Si motif is widely encountered in nature, although the synthetically derived combinations revolutionized industry. [1][2][3][4][5][6] This was driven by the versatility of siloxanes, which are used, among other things, as sealants, adhesives, coatings, plastics, cosmetics, etc. [7][8][9][10][11][12][13] In synthetic chemistry, siloxanes and silyl ethers also serve as very important reagents and building blocks.…”
Section: Introductionmentioning
confidence: 99%